Dampak Kenaikan Harga Gas LPG 3 Kg terhadap Kemampuan Rumah Tangga Miskin Dalam Pemenuhan Kebutuhan Hidup di Kelurahan Alalak Utara Kecamatan Banjarmasin Utara - Yulia Permata Sari; Chairul Sa’roni (PPJP Universitas Lambung Mangkurat, 2020)
The purpose of this study is to determine the amount of household expenditure that must be spent due to the 3kg LPG price increase, know the efforts of low households when there is an increase of 3kg LPG and to see the difference before or after the 3 kg LPG price increase in the North Alalak area North Banjarmasin. This research was conducted on low households in the northern alalak village, Banjarmasin north. The data used in the study are primary data and secondary data. This study's population were all low households in the northern alalak of Banjarmasin, which amounted to 1112 needy families. Whereas the number of samples can be obtained using the Yamane taro formula. Ninety-two respondents will be selected using simple random sampling techniques or simple random models. Each sampling unit in the population has the same opportunity to be chosen as a sample member. The study used a paired sample T-test. The t is equal to -9,279, smaller than T's cost, which is equivalent to 0.67720 with a significance value of 0.000 (p <α). The test results can be concluded that there are differences between before and after the increase in 3 kg LPG in North Alalak Village, North Banjarmasin.